THE EFFICIENCY OF WATER UTILIZATION ON VARIOUS THE LOCAL GRASSES WITH DIFFERENT WATER LEVELS - Paramartha, I Nyoman Bayu; Trisnadewi, Anak Agung Ayu Sri; Duarsa, Magna Anuraga Putra (Pastura; Vol 9 No 1 (2019): Pastura Vol. 9 No. 1 Tahun 2019, 2019)
This study aims to determine the efficiency of water utilization in the local grasses of Axonopus compressus, Paspalum conjugatum, and Oplismenus burmanni with different water levels. The study was conducted in the Laboratory of Greenhouse, Faculty of Animal Husbandry Udayana University, Denpasar. Completely randomized design of 3 × 3 nested patterns was used in this study with a type of grass treatment: Axonopus compressus, Paspalum conjugatum, Oplismenus burmanni, and water levels i.e 100% field capacity (KL) (K 1 ), 75% (KL) (K 2 ), and 50% (KL) (K 3 ) thus there are 9 treatment combinations namely PK 1 , PK 2 , PK 3 , OK 1 , OK 2 , OK 3 , AK 1 , AK 2 , dan AK 3 . Each treatment combination was repeated four times so there were 36 research pots. The variables observed were efficiency of water utilization, growth, production and growth characteristics. The results show that Paspalum conjugatum grass has the highest responsiveness on the efficiency of water utilization at giving different water levels compared to grass Axonopus compressus and Oplismenus burmanni. This study concluded that there was an increase in water utilization efficiency at the provision of 75% KL (K2) moisture content on grass Axonopus compressus and Paspalum conjugatum, whereas in grass Oplismenus burmanni the provision of different water content had no effect on improving water utilization efficiency. Key words: Axonopus compressus, Paspalum conjugatum, Oplismenus burmanii, water content, water utilization efficiency